Development and characterization of spiced chicken shell egg - Lorilla, Princess Marie Carmen
The main purpose of this study was to develop spiced chicken shell eggs (SCSE) through the application of pressure at the onset of soaking in order to facilitate diffusion of flavoring through the shell and in effect shorten the curing period.